Tradução para língua portuguesa (Brasil), adaptação cultural e validação do questionário de qualidade de vida parathyroid assessment symptoms em pacientes com doença renal crônica e hiperparatireoidismo - Campos, Rafael Costa e (2019)
Chronic kidney disease (CKD) is a disease with a high global prevalence associated with high morbidity and mortality, as well as loss of quality of life. Hyperparathyroidism is related to the progressive loss of renal function, where the decrease in blood calcium levels increases the secretion of the parathyroid hormone (PTH) by a compensatory mechanism. This change in calcium and PTH metabolism increases calcium uptake in bones with signs and symptoms of bone pain, fractures, and kidney stone formation. Hyperparathyroidism is also related to other manifestations such as headache, abdominal pain, depression and fatigue. The Parathyroid Assessment Symptoms questionnaire, as a tool for assessing quality of life in patients with hyperparathyroidism, aims to identify and quantify how important and disabling these symptoms are in patients with hyperparathyroidism. It is considered that having this instrument adapted to Portuguese language is of extreme clinical importance. Thus, the present study aimed to translate PAS into Portuguese (Brazil), cultural adaptation and validation of the instrument, in patients with secondary and tertiary hyperparathyroidism. A study carried out at the São Lucas Hospital of the Pontifical Catholic University of Rio Grande do Sul (PUCRS), with a sample of 100 patients between men and women who responded to PAS and Short Form Health 36 (SF-36), a generic quality assessment questionnaire of life. Analyzing the results of the PAS application, we present good instrument reliability through the properties of intraclass correlation coefficient and internal consistency (Cronbach's alpha coefficient).the results of the PAS application, we present good reliability of the instrument through the properties of reproducibility (intraclass correlation coefficient=0.83) and internal consistency (Cronbach's alpha coefficient>0.7). Through medium and high correlations, between the results of the PAS and SF-36 questions, construct validity criteria between the questionnaires were demonstrated. In conclusion, PAS translated from English to Portuguese (Brazil) was shown to have adequate reliability and validity. In addition, the instrument seems to be adapted to evaluate quality of life in patients diagnosed with hyperparathyroidism, with fluency in the Portuguese language.